The first familial case of inherited 2q37.3 interstitial deletion with isolated skeletal abnormalities including brachydactyly type E and short stature. (17th November 2014) - Jean‐Marçais, Nolwenn; Decamp, Matthieu; Gérard, Marion; Ribault, Virginie; Andrieux, Joris; Kottler, Marie‐Laure; Plessis, Ghislaine
<x xml:space="preserve">Abstract</x> Albright hereditary osteodystrophy (AHO)‐like syndrome is also known as brachydactyly‐mental retardation syndrome (BDMR; OMIM 60040). This disorder includes intellectual disability in all patients, skeletal abnormalities, including brachydactyly E (BDE) in approximately half, obesity, and facial dysmorphism. Patients with 2q37 microdeletion or HDAC4 mutation are defined as having an AHO‐like phenotype with normal stimulatory G (Gs) function. HDAC4 is involved in neurological, cardiac, and skeletal function. This paper reports the first familial case of 2q37.3 interstitial deletion affecting two genes, HDAC4 and TWIST2. Patients presented with BDE and short stature without intellectual disability, showing that haploinsufficiency of the HDAC4 critical region may lead to a spectrum of phenotypes, ranging from isolated brachydactyly type E to BDMR. © 2014 Wiley Periodicals, Inc.